Bioconcentration and Metabolism of Emodin in Zebrafish Eleutheroembryos - Chen, Jiefeng; Li, Shaodong; Liu, Mengping; Lam, Christopher Wai Kei; Li, Zheng; Xu, Xinjun; Chen, Zuanguang; Zhang, Wei; Yao, Meicun (Frontiers in Pharmacology, 2017)
Emodin is a major active anthraquinone of various herbal laxatives, which can exert many pharmacological effects. However, chronic use of anthranoid laxatives, even at low dosages, may cause melanosis coli (MC). It has been suggested that the accumulation of anthraquinones is a risk factor in the MC process. To investigate the accumulation of emodin, we conducted a bioconcentration study of emodin in zebrafish eleutheroembryos. Based on the economic cooperation and development (OECD) 305 test, zebrafish eleutheroembryos were exposed to emodin at a constant concentration for 48 h, before the test media were replaced by the blank medium for 24 h of depuration. To eliminate the effect of metabolism of emodin for assessment of the bioconcentration factor (BCF), we also conducted a modified test for which zebrafish eleutheroembryos were exposed to the non-renewed test media, whose emodin concentration decreased with time. At different exposure time points, zebrafish eleutheroembryos and exposure media were sampled for analysis of emodin concentration using HPLC-MS/MS. The results showed rapid accumulation of emodin in zebrafish eleutheroembryos to reach a steady-state concentration within 24 h. Meanwhile, emodin was actively metabolized by zebrafish eleutheroembryos to result in 29.5% to 40.7% of its elimination. In the groups with high or low concentrations of emodin, the standardized BCF (sBCF) values in the standard test were 24.0 and 20.0, while those in the modified test were 50.4 and 52.0. These results showed that emodin could accumulate in zebrafish eleutheroembryos when used for 48 h and beyond, suggesting that the accumulation of anthraquinones may be a risk factor in the MC process. Accordingly, emodin should be unsuitable for long-term use due to its accumulation.